Introducing a Framework for Developing Communication Skills of the Prospective English Teachers in the NCoEs of Sri Lanka - Indhurekhaa, T.; Neranjani, E.S. (University of Jaffna, 2025)
This is an ongoing research study to introduce a framework for developing the communication skills of the prospective English teachers in the National Colleges of Education (NCoEs) of Sri Lanka. Recognizing the shortage of skilled English language teachers in Sri Lanka, NCoEs were given the responsibility of producing competent teachers to teach English Language in the government schools. The English Language competence, mainly communication skills are essential for all English Language teachers because they are the only role model of communication and exposure for majority of the students in Sri Lanka. However, it was observed that majority of the NCoE qualified teachers did not have adequate communication skills. Research studies conducted on the NCoEs in Sri Lanka revealed that the majority of NCoE teachers did not develop English communication skills due to the issues in the NCoE curriculum. A preliminary study was also conducted on 25 NCoE teachers of English who have already been employed and identified the issues and challenges faced by them in the classroom. The study applied a qualitative dominant mixed design adopting qualitative and quantitative data collection tools. Informal interviews and classroom observations were conducted to obtain in-depth data from the prospective teachers while a structured questionnaire was administered to the employed teachers to identify their views, attitudes as well as challenges. The statistical and thematic analysis are used to analyse the data. This study is significant to fill the gap in the current studies. The findings are expected to provide valuable insight for developing the NCoE curriculum incorporating efficient communication practices of the framework for the prospective English language teachers.
Keywords: Framework; Prospective English language teachers; Communication skill; NCoEs